A STUDY OF WOMAN ENTREPRENEURS IN MANADO - Lengkong, Natalie C. (Sam Ratulangi University, 2016)
Entrepreneurship is in all areas of our life. Entrepreneurs play a key role in economic growth and job creation of a country. Successful women are becoming more prominent in our society. Woman entrepreneurs had become the contributors to todayâ€™s business. Not much is known about what make woman entrepreneurs gain success in their entrepreneurial process. Qualitative methodology was used to conduct this research. Descriptive-exploratory study which used to explore key factors that motivated woman become entrepreneur and the challenges and problems faced by woman entrepreneurs. â€œSocial situationâ€ as the population. In-depth interview were used in observation to collect some important information from business owner. The result is key factors that motivated woman in ManadoÂ become an entrepreneur which are business capital, desire for independent, business opportunity, family business, hobby, perspective, larger income, inspiration, level of education, work environment, self esteem, family environment and neighborhood. Besides, woman entrepreneurs still faced challenges and problems regarding on time management, competition, customer satisfaction, marketing strategy, innovation, financial management and employee training. To deal those problems is only comes as a result of initiatives by the woman entrepreneur herself.